Allosteric inhibition of c-Met kinase in sub-microsecond molecular dynamics simulations induced by its inhibitor, tivantinib. Issue 15 (31st March 2016) - Yan, Maocai; Wang, Huiyun; Wang, Qibao; Zhang, Zhen; Zhang, Chunyan
Abstract : Molecular dynamics simulations showed that conformation transition of c-Met from DFG-in to DFG-out may accomplish rapidly in the presence of tivantinib. A unique binding mode of tivantinib was found to be critical for this "DFG-flip". Abstract : Protein dynamics in the allosteric regulation of enzymes is crucial for understanding the regulation mechanism of enzymes and designing of inhibitors. Kinases have a conserved Asp–Phe–Gly motif (DFG motif) whose conformation determines the activation state of the kinase; however, knowledge on conformational transition of the DFG motif from the active state to the inactive state ("DFG-flip") is quite limited. Here we report a DFG-flip of c-Met kinase in molecular dynamics (MD) simulations, induced by its allosteric inhibitor tivantinib. Our MD simulations showed that, with the assistance of tivantinib, c-Met may transit from the DFG-in state to the DFG-out state in a sub-microsecond time-scale. A unique binding mode of tivantinib to c-Met was identified to be the key intermediate for the ligand-induced DFG-flip. This study provides a detailed process of inhibitor-induced kinase allostery, as well as important insights into the DFG-flip mechanism and the design of allosteric inhibitors, not only of c-Met, but also of other kinases.